TINJAUAN YURIDIS TERHADAP PERJANJIAN BANGUN BAGI (STUDI PADA PEMBANGUNAN RUMAH TOKO OLEH DEVELOPER PERORANGAN DI KECAMATAN MEDAN SELAYANG) - RACHEL SHEILA SITORUS (PREMISE LAW JURNAL, 2016)
Construction sharing agreement is an agreement between a land owner and the second party, a developer. The second party is given the right to work on the land, on condition that the profits are divided into two:for the land owner and the developer. In the process of implementing construction sharing agreement, there will be many problems between the two parties so that legal protections is needed in order to forestall and handle the problems.The result of the research showed that construction sharing agreement of the construction of a shop-house in Medan Selayang Subdistrict between Mrs. X and Mr. Y was a consensus and reciprocal agreement It was found that in its implementation it caused the complaint about indemnity and the cancellation of the contract. Keywords: Construction Sharing Agreement, Problem, Legal Protection